The Affect Of Nasimi’s Heritage In Mirze Jahanshah Haqiqi’s Creation - Мурaдовa, Ш. Г. (Journal of Oriental Studies, 2018)
In this article the investigator had investigated Mirze Jahanshah’s Haqiqi creation and had compared his creation with Nasimi’s poems.The investigator had grounded on these examples brought from Haqiqi’s gazells which promote the idea of Haqiqi’s hurufism, reflection of the idea of hurufism in the poetry.